117k views
1 vote
The graph represents the function f(x) = x2 + 3x + 2. If g(x) is the reflection of f(x) across the x-axis, g(x) = . (Write the function in standard form. Use ^ to indicate an exponent.) Reset Next

User Max Travis
by
5.4k points

1 Answer

7 votes

Answer:

g(x) = - (x² + 3x + 2) = - x² - 3x - 2

Explanation:

The graph represents the function f(x) = x² + 3x + 2.

Now, g(x) is the function which is obtained by reflecting f(x) across the x-axis.

While a graph of a function reflects across x-axis then its y-values will change sign for a fixed value of x.

Therefore, the function g(x) will be given by

g(x) = - (x² + 3x + 2) = - x² - 3x - 2 (Answer)

User Lakhwinder Singh
by
5.9k points